Physical characterization of um-cajá genotypes fruits (Spondias sp.) - Silva, Leirson Rodrigues da (Revista de Ciências Agroveterinárias, 2014)
The “umbu-cajá” is a spontaneous occurrence of fruit trees in the semi-arid Northeast, where their fruit is harvested in an explorative method. This work aimed to evaluate the quality of umbu-Brazil (Spondias sp.), from different genotypes, through physical characterization. The harvest was carried out in Iguatu, CE, in the month of March 2007, and the fruit was removed with the help of a hook, at the stage of commercial maturity, where the sign of maturity was the yellow orange color of the peel. The 20 genotypes of following parameters were evaluated: fresh mass, diameter, size, yield (peel+pulp), and fi rmness of pulp. Variation was observed among genotypes for all twenty physical characteristics evaluated. The fruits of the genotypes evaluated and harvested at maturity (yellow orange peel) presented a mean value of 2.36 pulp fi rmness, diameter of 27.32 mm, size of 30.36 mm, fresh mass from 14.51 g and an excellent yield of pulp (above 80%) highlighting P5, P15, P17, this factor of great importance for processing.